Comprehensive medical, social and psychological assistance to elderly people with dementia in wartime and post-war recovery: problems and solutions (Environment & Health, 2025)
The aim of the study is to analyze the current situation regarding the need for comprehensive medical, social and psychological care for older people with cognitive disabilities and the market for medical and social services in this area.Materials and methods. To achieve the goal, information-analytical and systematic methods of analysis were used based on information from official sources, media and social network data, as well as scientific publications on the topic of the study.Results. The need to develop and implement a modern model of organizing comprehensive care for elderly people suffering from dementia and their family members in the context of war and post-war sociodemographic transformations is shown. Special attention is paid to the impact of military operations on the availability of resources, the psycho-emotional state of elderly patients and their environment. A scientific review of modern approaches to creating a communications system in comprehensive care for patients with dementia is conducted in order to analyze the current state of development and implementation of communication technologies, identify trends and dynamics of their development. The importance of an interagency approach is emphasized, which includes medical, psychological, social and legal support, as well as adaptation of infrastructure and personnel training to changing conditions. Recommendations are given for building a sustainable and flexible care system in the context of modern challenges.Conclusions. The problem of creating appropriate conditions for this target group is very urgent. The solution requires a complete rethinking of stereotypes and, first of all, the creation of a state system of care for people with mental disorders (in particular, with dementia). It should include all forms of care: information centers, home care centers, day care centers for the elderly, family respite departments and nursing inpatient facilities andoperate in a single interdepartmental space, ensuring an improvement in the quality of life and respect for human rights and freedoms.
Keywords: post-war consequences; socio-demographic changes; dementia patients; comprehensive care; foreign experience; communication technologies; deinstitutionalization; educational and methodological training